EFFECT OF STOCKING DENSITY ON DEVIATION FROM BILATERAL SYMMETRY AND SLAUGHTER WEIGHT IN BROILERS - H. Mirtagioglu; A. Mollaoğulları; S. Genç; M. Mendeş (Journal of Animal and Plant Sciences, 2013)
The main objective of this study was to investigate the effect of two different stocking densities (11 birds / m2 and 17 birds / m2) on deviation from bilateral symmetry in broiler chickens. For this purpose, the weekly body weight, left and right shank length, shank width, wing length, face width and face length of the same birds were measured on from 7th to 42nd days of age. Repeated measurements analysis of variance was used to investigate the effect of stocking densities and ages (week) on relative asymmetry. Binary logistic regression analysis was used to determine the most important morphological character influencing the deviation from ideal slaughter weight of 1800 g. The overall relative asymmetry mean for shank width was significantly greater in control group (2.42±0.41) than in treatment group (1.87±0.43). The results of binary logistic regression analysis showed that only increase in difference of width in left and right shank caused significant change (p=0.0148) in slaughter weight. In this study, the deviation from the bilateral symmetry was mostly found in fluctuating asymmetry for the measured characters in treatment group (11 birds per m 2), and the low fluctuating asymmetry level was generally indicated higher welfare level and lower developmental instability for this group than that of the control group (17 birds per m 2). Stocking density can be stated as one of the most important environmental factors which may influence developmental stability, welfare and performance of broilers.
Keywords: Stocking density and bilateral symmetry; logistic regression; morphological traits